MAKNA ADAT MANJOPUIK LIMAU DI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Permana, Muhammad Iqbal; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Perahu Begandung a culture from the Kuantan Mudik sub-district, Perahu Baganduang is held for Manjopuik Limau, Manjopuik Limau is a tradition of single girls in groups or individually visiting a girl's house with the aim of looking for mate or just to stay in touch and enliven the Eid al-Fitr holiday, where before this event is held the men in one of the villages have appointed a woman for Manjopuik Limau, This study uses a qualitative research method with a descriptive approach. The informants in this study were community leaders, traditional elders and indigenous people of Lubuk Jambi, using the snowball technique. Data collection techniques were carried out by means of observation, interviews and documentation. For data analysis techniques using interactive data analysis techniques Miles and Huberman. While the data validity checking technique uses extension of participation and triangulation. The results of this study indicate that the traditional figures of Kenegerian Lubuk Jambi interpret the Manjopuik Limau tradition as a tradition that can build unity and togetherness between the tradition actors and the community. The people of Kenegerian Lubuk Jambi participate and work together in organizing the Manjopuik Limau tradition. The Manjopuik Limau tradition can also embrace young people in creating good relationships because in its implementation this tradition highly upholds religious values and customary norms. Keyword: Culture, baganduang boat, lubuk jambi, manjopuik limau